1960
DOI: 10.1002/food.19600040102
|View full text |Cite
|
Sign up to set email alerts
|

Reaktionsmechanismus und Kinetik der Umesterung von Fetten. 1. Mitteilung über Umesterungsreaktionen

Abstract: Die Umesterung von Fetten ist ein altbekanntes Behandlungsverfahren. Gleichwohl ist es erst in jiingster Zeit zu u-achsender Bedeutung gekommen, nachdem es gelungen ist, den Reaktionsmechanismus aufzuklaren, hochaktive Katalysatoren aufzufinden und in die reaktionskinetischen Verhaltnisse einzudringen, kurzum den ProzeS theoretisch und praktisch zu beherrschen. Um diese Fortschritte zu verdeutlichen, sei nur auf die fruheren, robusten Reaktionsbedingungenhohe Behandlungstemperatur und trage Katalysatorenhingew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1961
1961
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…In 1960, Baltes suggested a reaction mechanism for the base-catalysed ester interchange reaction between triglycerides (Baltes, 1960). This mechanism assumed a glycerolate anion to be the catalytically active intermediate.…”
Section: Remaining Questions Concerning the Interesterification Processmentioning
confidence: 99%
“…In 1960, Baltes suggested a reaction mechanism for the base-catalysed ester interchange reaction between triglycerides (Baltes, 1960). This mechanism assumed a glycerolate anion to be the catalytically active intermediate.…”
Section: Remaining Questions Concerning the Interesterification Processmentioning
confidence: 99%
“…At about the same time as Baltes [7] suggested his mechanism, Weiss et al [8] suggested a different mechanism whereby in a first step an enolate anion is formed according to figure 3. Subsequently, this enolate anion reacts further with a fatty acid moiety to form a b-keto ester, which they considered to be the "active catalytic constituent" (figure 4).…”
Section: Formation Of An Enolate Anionmentioning
confidence: 99%
“…It was not until 1960 that Baltes [7] proposed that this "active catalyst constituent" could well be the glycerolate anion. He suggested that this be formed by the reaction of the sodium methanolate anion with a triacylglycerol molecule according to figure 1. …”
Section: Early Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations